2015
DOI: 10.1021/acs.orglett.5b00172
|View full text |Cite|
|
Sign up to set email alerts
|

Microbacterins A and B, New Peptaibols from the Deep Sea Actinomycete Microbacterium sediminis sp. nov. YLB-01(T)

Abstract: Two new peptaibols, namely microbacterins A (1) and B (2), were isolated from the deep sea inhabited actinomycete Microbacterium sediminis spp. nov. YLB-01(T). The sequences of the amino acid residues were determined on the basis of intensive NMR and ESI-MS/MS spectroscopic analysis, in addition to the Marfey's method and CD and optical rotation data for the configurational assignment. Both 1 and 2 exhibited significant cytotoxic activities against a panel of human tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 23 publications
2
42
0
2
Order By: Relevance
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
“…T2, the fungus was grown in several types of broth media. Growth of the fungus in a modified potato dextrose broth (PDB) resulted in the generation of numerous new and known members of the malettinin family of polyketides [malettinins A (27), B (28), and F-H (16)(17)(18)(19)(20), respectively] ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations